Transport of Russian Federation: Problems and Trend of Its Development - Ilya Gennadievich Tkachev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article presents the analysis of the development of transport of Russian Federation on the present stage using a set of indicators in dynamics: the number of transport organizations, revenues and profits, the volume of cargo and passengers, length of the transport ways, number of transport vehicles, investment in fixed capital; the analysis of the main documents for development of the transport complex; the main trends and problems of development of transport of the country.